Outcomes following Naloxone Administration by Bystanders and First Responders. (2nd November 2021) - Farkas, Andrew; Westover, Rachael; Pizon, Anthony F.; Lynch, Michael; Martin-Gill, Christian
Abstract: Background : Naloxone is widely available to bystanders and first responders to treat patients with suspected opioid overdose. In these patients, the prognostic factors and potential benefits associated with additional naloxone administered by emergency medical services (EMS) are uncertain. Objectives : We sought to identify prognostic factors for admission to the hospital following prehospital administration of naloxone for suspected opioid overdose by bystanders and first responders. We secondarily examined whether administration of additional naloxone by paramedics after initial treatment by non-EMS personnel was associated with improvement in level of consciousness prior to hospital arrival. Methods : This is a retrospective cross-sectional study of patients treated within a single urban EMS system from 2013 to 2016. Inclusion criteria were administration of naloxone by bystanders or first responders and transport to one of three academic medical centers. For the secondary analysis, only patients with a Glasgow Coma Scale (GCS) score ≤12 on paramedic arrival were included. We performed univariate and multivariable analyses examining a primary outcome of hospital admission and secondary outcome of improvement in consciousness as defined by GCS >12 in patients with initial GCS ≤12. Results : Of 359 patients identified for the primary analysis, 60 were admitted to the hospital. Factors associated with increased rate of admission included higher total naloxone dosage (OR 1.36, 95% CI 1.09–1.70) and presence of alternate/additional non-opioid central nervous system (CNS) depressants (OR 2.51, 95% CI 1.13–5.56). Among 178 patients who had poor neurologic status (GCS ≤12) on paramedic arrival following naloxone administered by bystander or first responder, administration of additional naloxone was not associated with a better rate of neurologic improvement prior to hospital arrival (77% improved with additional naloxone, 81% improved without additional naloxone; OR 0.82, 95% CI 0.39–1.76). Conclusions : Among patients with suspected opioid overdose treated with naloxone by bystanders and first responders, a higher total dose of naloxone and polysubstance intoxication with additional CNS depressants were predictors of admission. Administration of additional naloxone by paramedics was not associated with a higher rate of neurologic improvement prior to hospital arrival, suggesting a ceiling effect on naloxone efficacy in opioid overdose.